Regional Geobarometry in the Contact Aureoles of the Anorthositic Nain Complex, Labrador - BERG, JONATHAN H. (Journal of Petrology, 1977)
The 1.4 Gyr anorthositic Nain complex was emplaced by multiple intrusion into Archean and Aphebian rocks whose metamorphic grades range regionally from greenschist to granulite and whose temperature at the time of emplacement was probably no higher than ∼200–300 °C. Using experimental data on Ga-Cd and Hy-Ol-Qz equilibria, compositional studies allow the determination of contact metamorphic pressures and temperatures for samples over an area > 10,000 km2. The results indicate that for these specimens temperatures ranged from ∼645° to 915 °C and pressures ranged from about 3.7 to 6.6 kbar. Locally, original garnet porphyroblasts have partially reacted to produce symplectites of cordierite+hypersthene, resulting in a corona-like texture. These textures and associated mineral zoning indicate that some of the specimens have experienced a polymetamorphic history. This poly metamorphism presumably resulted from the multiple intrusions of magmas of the Nain complex. The regional distribution of pressures appears systematic and suggests an arch in the ancient pressure surfaces (paleo-isobars). This postulated arch, which trends WNW-ESE, roughly coincides with a proposed graben structure in the Conrad discontinuity based on gravity studies (Stephenson, 1974). The association of these two features can be rationalized with a mechanism of incipient continental rifting. The emplacement of the unmetamorphosed northern Labrador anorthosite massifs in a non-orogenic environment of low temperature and moderate depth suggests that the metamorphosed anorthosites south of the Grenville Front may have been accidental participants in a post-anorthosite Grenville orogeny and metamorphism.